"Visible" Phase Separation of MAPbI3/δ‐FAPbI3 Films for High‐Performance and Stable Photodetectors. Issue 12 (14th May 2021) - Shang, Meijia; Lian, Gang; Lv, Song; Zhu, Fei; Wang, Qilong; Cui, Deliang; Zheng, Zhaoke; Huang, Baibiao
Abstract: Simultaneous achievement of elevated photocurrent by increasing grain size of perovskite films and reduced dark current by introducing passivation phase as well as improved stability is significant and tough challenge for perovskite‐based photodetector devices. Herein, in‐situ formation of "visible" formamidinium lead iodide (δ‐FAPbI3 ) phase within a high‐quality methylamine lead iodide (MAPbI3 ) film is reported by a pressure‐induced phase separation strategy. The MAPbI3 single‐crystal grains are adequately grown and parts of them are over 20 µm in lateral dimension. More importantly, the incursion of δ‐FAPbI3 with high resistance behaves like an organic scaffold to passivate the trap state, limit cation diffusion, and increase intrinsic resistance of the MAPbI3 film. Accordingly, the MAPbI3 /δ‐FAPbI3 photodetector devices exhibit excellent photoelectrical performance, including high detectivity, responsivity, and on/off ratio due to long carrier lifetime and low defect density. Furthermore, the unsealed MAPbI3 /δ‐FAPbI3 film device retains over 94% of its initial photocurrent after 15 days in ambient conditions, exhibiting significantly improved stability. The introduction of "useless" δ‐FAPbI3 phase in high‐quality perovskite films opens up a new way toward improved photoelectrical performance and stability. Abstract : A high‐quality MAPbI3 film with "visible" δ‐FAPbI3 phase is prepared via pressure‐induced ion migration and secondary crystal growth mechanism. The optimized MAPbI3 /δ‐FAPbI3 film photodetector simultaneously achieves enhanced light current, reduced dark current, and superior stability compared to that of pure high‐quality MAPbI3 film photodetector.